Unraveling Core Functional Microbiota in Traditional Solid-State Fermentation by High-Throughput Amplicons and Metatranscriptomics Sequencing - Song, Zhewei; Du, Hai; Zhang, Yan; Xu, Yan (Frontiers in Microbiology, 2017)
Fermentation microbiota is specific microorganisms that generate different types of metabolites in many productions. In traditional solid-state fermentation, the structural and functional changes in core microbiota influence the quality and quantity of products. As typical food fermentation, Chinese Maoti-flavor liquor production has the particular mechanism with complex microorganisms and wide variety of metabolites. However, it remains unclear that species succession and function shift of core microbiota in this traditional food fermentation. Here, high-throughput amplicons (16S rRNA gene amplicons sequencing and internal transcribed space amplicons sequencing) and metatranscriptomics sequencing technologies are combined to reveal the structure and function of core microbiota in Chinese Maoti-flavor liquor production. In addition, ultra-performance liquid chromatography and headspace-solid phase microextraction-gas chromatography-mass spectrometer are employed to quality and qualitative analysis the major flavor metabolities. Amplicons analysis indicates species distribution of core micorbiota includes 10 fungal and 11 bacterial genera. Besides, metatranscriptomic analysis indicates pyruvate metabolism in yeasts (genera Pichia, Schizosaccharomyces, Saccharomyces and Zygosaccharomyces) and lactic acid bacteria (genus Lactobacillus) reflects different stages in production of flavor components. Overall, these findings have shown that there are two stages in production. Stage I is high-level alcohol (ethanol) production period that genus Schizosaccharomyces serves as the core functional microorganism. Stage II is high-level acid (lactic acid and acetic acid) production period that genus Lactobacillus serves as the core functional microorganism. Furthermore, functional shift from genus Schizosaccharomyces to genus Lactobacillus drives flavor components conversion from alcohol (ethanol) to acid (lactic acid and acetic acid) in Chinese Maotai-flavor liquor production. This study provides new attempts to understand the effects of core functional microbiota in Chinese Maotao-flavor liquor production and explore the fermentation microbiota under different environmental conditions further.